PERANCANGAN BAHASA VISUAL DALAM PENCIPTAAN KARYA FILM PENDEK DARA DALAM BELENGGU - Thoriq Sihabudin; I Made Denny Chrisna Putra; I Nyoman Payuyasa (CALACCITRA: JURNAL FILM DAN TELEVISI, 2026)
Film is an audio-visual medium that possesses the power to convey meaning through moving images; however, strictly relying on verbal dialogue or verbalism remains a common issue in practice. The creation of the short fiction film Dara dalam Belenggu addresses the psychological issue of body anxiety in adolescents, demanding a specific visual approach to depict internal conflict without explicit verbal explanation. This article discusses the application of Cinematic Language by the cinematographer as a narrative solution to visualize the isolation and mental pressure experienced by the protagonist, Anari. The creation method focuses on Shot Design utilizing Negative Space and the application of lighting with a Progressive Contrast Ratio. The results demonstrate that the use of tight, restrictive framing (claustrophobic) and the shift in light contrast ratio from flat to high contrast successfully represent the emotional escalation and the character's feeling of being "shackled" symbolically. Through this approach, visual elements effectively function as the primary storyteller, building the atmosphere and character emotion..